Observational Analytic Study on Craniofacial Growth Changes in Developing Skeletal Class II Malocclusion with a Retrognathic Mandible Patients Using Myobrace - Erwansyah, Eka; Nur, Muhammad Kamil; Hidayati, Nasyrah; Habar, Eddy Heriyanto; Pawinru, Ardiansyah S.; Ranggang, Baharuddin M. (European Journal of General Dentistry, 2025)
Myofunctional appliances have been used for correction of developing craniofacial. One of the frequently used is Myobrace. This study aims to assess the effects of the Myobrace appliance on craniofacial growth modifications in developing patients with skeletal class II malocclusion.The research subjects totaled 11 children with predetermined criteria. Subjects were all patients who were being treated with Myobrace (prefabricated myofunctional appliance, Myofunctional Research Co., Australia) at orthodontic clinic of the Hasanuddin University Dental and Oral Hospital. Lateral cephalograms were taken for all patients before and after treatment (4 months later). The effects of the appliances on the craniofacial growth were assessed using five linear measurements (anterior craniofacial height [N-Me], posterior craniofacial height [S-Go], cranial base length [S-N], maxillary length [PNS-A], and mandibular length [Go-Pog]) before and after treatment.The normality test for data utilized the Shapiro–Wilk test to ascertain the analytical applicability of the standard data distribution. The paired samples t-test was used to assess different parameters between before and after treatment. The threshold for significance was at p-value of < 0.05. Data were analyzed via IBM SPSS for Windows.It was found that there was a significant change in posterior craniofacial height (S-Go), maxillary length (PNS-A), and mandibular length (Go-Pog), relationship of the mandible relative to the cranial base (SNB) values before and after treatment, and also the ANB values before and after treatment of 2.63 and 1.9 degrees, respectively. There was no significant change in anterior craniofacial height (N-Me) and cranial base length (S-N).Myofunctional treatment with Myobrace appliance can help overcome class II skeletal malocclusion with retrognathic mandible during the growth period and help craniofacial growth by improving tongue position, breathing, correcting malocclusion, improving orofacial muscle function, and facial development.
Keywords: craniofacial growth; Myobrace; myofunctional; retrognathic mandible; skeletal class II malocclusion